Young girls’ perception of beauty in disney princesses’ movies - Nor Jijidiana, Azmi; Radzuwan, Ab Rashid; Zanirah, Wahab (2017)
The Disney princesses’ characters are icons for young girls. Their admiration towards the characters can be seen through their preference in movies selection and also their familiarity of each character in Disney animated films. Concern occurs when Disney animated films are always associated with beauty is good stereotype. The protagonists in the movies are always associated with beauty and positive qualities while the antagonist posses all the negative traits. Thus this study is conducted to 1) identify how young girls in Malaysian context justify beauty based on Disney princess characters and 2) whether they are influenced with the stereotypical ideology that Disney represented – beauty is good. An interview was conducted with 10 participants aged 4 to 6 years old in a kindergarten in Kuala Terengganu, Malaysia. Finding of the interview shows that the young girls define beauty in physical appearance and positive traits.